UTP – Gated Signaling Pathways of 5-HT Release from BON Cells as a Model of Human Enterochromaffin Cells - Liñán-Rico, Andromeda; Ochoa-Cortes, Fernando; Zuleta-Alarcon, Alix; Alhaj, Mazin; Tili, Esmerina; Enneking, Josh; Harzman, Alan; Grants, Iveta; Bergese, Sergio; Christofi, Fievos L. (Frontiers in Pharmacology, 2017)
Background: Enterochromaffin cells (EC) synthesize and release 5-HT and ATP to trigger or modulate gut neural reflexes and transmit information about visceral / pain sensation. Alterations in 5-HT signaling mechanisms may contribute to the pathogenesis of IBD or IBS, but the pharmacologic or molecular mechanisms modulating Ca2+-dependent 5-HT release are not understood. Previous studies indicated that purinergic signaling via ATP and ADP is an important mechanism in modulation of 5-HT release. However, EC cells also respond to UTP and UDP suggesting uridine triphosphate receptor and signaling pathways are involved as well. We tested the hypothesis that UTP is a regulator of 5-HT release in human EC cells. Methods: UTP signaling mechanisms were studied in BON cells, a human EC model, using Fluo-4/Ca2+imaging, patch-clamp, pharmacological analysis, immunohistochemistry, western blots and qPCR. 5-HT release was monitored in BON or EC isolated from human gut surgical specimens (hEC). Results: UTP, UTPS, UDP or ATP induced Ca2+oscillations in BON. UTP evoked a biphasic concentration-dependent Ca2+response. Cells responded in the order of UTP, ATP>UTPS>UDP>>MRS2768, BzATP, me-ATP>MRS2365, MRS2690, NF546. Different proportions of cells activated by UTP and ATP also responded to UTPS (P2Y4, 50% cells), UDP (P2Y6, 30%), UTPS and UDP (14%) or MRS2768 (<3%). UTP Ca2+responses were blocked with inhibitors of PLC, IP3R, SERCA Ca2+pump, La3+sensitive Ca2+channels or chelation of intracellular free Ca2+ by BAPTA/AM. Inhibitors of L-type, TRPC, ryanodine-Ca2+pools, PI3-Kinase, PKC or SRC-Kinase had no effect. UTP stimulated voltage-sensitive Ca2+currents (ICa), Vm-depolarization and inhibited IK (not IA) currents. An IKv7.2/7.3 K+ channel blocker XE991 mimicked UTP-induced Vm-depolarization and blocked UTP-responses. XE-991 blocked IK and UTP caused further reduction. La3+ or PLC inhibitors blocked UTP depolarization; PKC inhibitors, thapsigargin or zero Ca2+buffer did not. UTP stimulated 5-HT release in EC expressing TPH1, 5-HT, P2Y4/P2Y6R. Zero-Ca2+buffer augmented Ca2+responses and 5-HT release. Conclusions: UTP activates a predominant P2Y4R pathway to trigger Ca2+oscillations via internal Ca2+mobilization through a PLC/IP3/IP3R/SERCA Ca2+signaling pathway to stimulate 5-HT release; Ca2+influx is inhibitory. UTP-induced Vm-depolarization depends on PLC signaling and an unidentified K channel (which appears independent of Ca2+oscillations or Ica/VOCC). UTP-gated signaling pathways triggered by activation of P2Y4R stimulate 5-HT release.